Strengthening Digital Literacy Through Computer Science Education: Community Collaboration in Sydney, Australia - Shuwen Zhou (CV Edujavare Publishing, 2025)
The rapid advancement of digital technology has transformed communication, education, and professional interaction in modern society. As digital transformation continues to influence various sectors, digital literacy and computer science education have become essential competencies for individuals and communities. This community service program aims to strengthen digital literacy through computer science education and collaborative community engagement in Sydney, Australia. The program employed a qualitative participatory approach involving students, educators, and community members through workshops, mentoring sessions, collaborative digital learning, and practical computer science activities. Participants were introduced to digital communication platforms, computational thinking concepts, collaborative technologies, and ethical digital practices to improve technological competence and responsible digital participation. The results demonstrated that participants experienced significant improvement in communication skills, technological understanding, collaborative learning abilities, and confidence in utilizing digital platforms for educational and professional purposes. In addition, the implementation of collaborative learning activities encouraged active participation, problem-solving competence, and awareness of cyber security and information verification practices. Despite challenges related to technological inequality and varying levels of digital competence, continuous mentoring and participatory educational strategies contributed positively to the success of the program. Overall, the implementation of computer science education through community collaboration in Sydney provides valuable opportunities for improving digital literacy, strengthening community empowerment, and supporting technological readiness in the contemporary digital era. The collaborative approaches implemented in Sydney can also serve as important references for developing sustainable digital literacy programs in educational and community service contexts worldwide.